Powrót do równowagi psychicznej po doświadczeniu straty dziecka = Psychological recovery after the loss of the child - Trepka-Starosta, Justyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This paper discusses issues related to grief after the death of the child, participation in support groups and its role in the process of coping with loss. The aim is to present how this participation affects the difficult process of mourning, how better undestranding of the grief can help with coping with loss. This article preseanted such issues as: social support, role and benefits of support groups, predisposition of orphaned to choose adequate forms of assistanceas well as recommendations for people who can help them.
Keywords: śmierć dziecka; żałoba; radzenie sobie ze stratą; grupy wsparcia; wsparcie społeczne; death of the child; mourning; coping with loss; support group; social support